Implementation of Medan Mayor Regulation No. 53/2018 on Community Empowerment in Medan Petisah Sub-district - Aswin; Syafruddin Ritonga; Isnaini (MultiTech Publisher, 2024)
This paper examines the implementation of Mayor of Medan Regulation No. 53 of 2018 on Coordination and Implementation of Community Empowerment in Medan Petisah District in 2024. The research method used is descriptive with a qualitative approach, employing direct observation and interviews with local government officials as data sources. The findings indicate that this regulation serves as a crucial foundation for implementing community empowerment programs at the local level. Concrete steps have been established to enhance community participation, improve public service quality and infrastructure, and conduct routine evaluations to ensure program sustainability. Emphasis on effective coordination, community outreach, and improving administrative program understanding helps address implementation challenges. The regulation also governs fund allocation for infrastructure to ensure efficient resource utilization. Overall, the Coordination and Implementation of Community Empowerment in Medan Petisah District, in accordance with Mayor of Medan Regulation No. 53 of 2018, provides the basis for successful and effective community empowerment programs.